Use of disposable plastic cups in the composition of the mix for the production of ecological brick (Research, Society and Development, 2021)
Faced with the growth of environmental impacts in the world we are seeking and improving sustainable materials for use in civil construction. Among the materials we have the ecological brick, this reduces pollution since the manufacturing process, because it does not need burning, it is not necessary to feed the ovens by avoiding deforestation. It consists of sand, cement and water. The construction made with this brick presents pleasant temperatures inside, very well supporting the high temperatures. The present work aims to add crushed disposable cups aiming at improving the characteristics and properties of the ecological brick, where specimens will be molded to obtain the results. The ecological bricks with 0%, 40% and 60% percentages of crushed disposable cups were submitted to tests of compressive strength and water absorption. After performing the mechanical tests and characterization of the material in the laboratories of UNIFSA and PPGEM, it was observed that it is possible to use crushed disposable cups as a component for the ecological brick still according to the results obtained, only the formulation with 40% of cups addition meets the requirements set out in the NBR8491/12 standards and in NBR8492/12.